Somatic Editing of Ldlr With Adeno-Associated Viral-CRISPR Is an Efficient Tool for Atherosclerosis Research. Issue 9 (September 2018) - Jarrett, Kelsey E.; Lee, Ciaran; De Giorgi, Marco; Hurley, Ayrea; Gillard, Baiba K.; Doerfler, Alexandria M.; Li, Ang; Pownall, Henry J.; Bao, Gang; Lagor, William R.
Abstract : Objective—: Atherosclerosis studies in Ldlr knockout mice require breeding to homozygosity and congenic status on C57BL6/J background, a process that is both time and resource intensive. We aimed to develop a new method for generating atherosclerosis through somatic deletion of Ldlr in livers of adult mice. Approach and Results—: Overexpression of PCSK9 (proprotein convertase subtilisin/kexin type 9) is currently used to study atherosclerosis, which promotes degradation of LDLR (low-density lipoprotein receptor) in the liver. We sought to determine whether CRISPR/Cas9 (clustered regularly interspaced short palindromic repeats-associated 9) could also be used to generate atherosclerosis through genetic disruption of Ldlr in adult mice. We engineered adeno-associated viral (AAV) vectors expressing Staphylococcus aureus Cas9 and a guide RNA targeting the Ldlr gene (AAV-CRISPR). Both male and female mice received either (1) saline, (2) AAV-CRISPR, or (3) AAV-hPCSK9 (human PCSK9)-D374Y. A fourth group of germline Ldlr-KO mice was included for comparison. Mice were placed on a Western diet and followed for 20 weeks to assess plasma lipids, PCSK9 protein levels, atherosclerosis, and editing efficiency. Disruption of Ldlr with AAV-CRISPR was robust, resulting in severe hypercholesterolemia and atherosclerotic lesions in the aorta. AAV-hPCSK9 also produced hypercholesterolemia and atherosclerosis as expected. Notable sexual dimorphism was observed, wherein AAV-CRISPR was superior for Ldlr removal in male mice, while AAV-hPCSK9 was more effective in female mice. Conclusions—: This all-in-one AAV-CRISPR vector targeting Ldlr is an effective and versatile tool to model atherosclerosis with a single injection and provides a useful alternative to the use of germline Ldlr -KO mice. Abstract : Supplemental Digital Content is available in the text.